1999
DOI: 10.1093/jac/44.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Rhodamine 6G efflux for the detection of CDR1-overexpressing azole-resistant Candidaalbicans strains

Abstract: We investigated the drug efflux mechanism in azole-resistant strains of Candida albicans using rhodamine 6G (R6G). No significant differences in R6G uptake were observed between azole-sensitive B2630 (9.02 +/- 0.02 nmol/10(8) cells) and azole-resistant B67081 (8.86 +/- 0.03 nmol/10(8) cells) strains incubated in glucose-free phosphate buffered saline. A significantly higher R6G efflux (2.0 +/- 0.21 nmol/10(8) cells) was noted in the azole-resistant strain (B67081) when glucose was added, compared with that in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
117
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(122 citation statements)
references
References 11 publications
5
117
0
Order By: Relevance
“…31,39) In the present study, we used a fluorescent dye, rhoamine 6 G (R6G), which is a substrate of CDR1, to identify CDR activity because a previous study showed that the efflux of rhoamine 6 G is positively correlated with the expression of CDR1. 40) Our results for rhodamine 6 G active efflux also showed that with the susceptibilities of the strains to FLC decreased, and the extrusion of rhodamine 6 G by C. albicans increased in the presence of glucose providing energy for rhodamine 6 efflux (Fig. 6), which suggested CDR1 overexpression contributed to the development of the reduction susceptibilities to FLC by FLC exposure in this study.…”
Section: Discussionsupporting
confidence: 72%
“…31,39) In the present study, we used a fluorescent dye, rhoamine 6 G (R6G), which is a substrate of CDR1, to identify CDR activity because a previous study showed that the efflux of rhoamine 6 G is positively correlated with the expression of CDR1. 40) Our results for rhodamine 6 G active efflux also showed that with the susceptibilities of the strains to FLC decreased, and the extrusion of rhodamine 6 G by C. albicans increased in the presence of glucose providing energy for rhodamine 6 efflux (Fig. 6), which suggested CDR1 overexpression contributed to the development of the reduction susceptibilities to FLC by FLC exposure in this study.…”
Section: Discussionsupporting
confidence: 72%
“…We similarly investigated R6G, a fluorescent substrate of many ABC transporters that has been used to study the functions of Cdr1p and Cdr2p in S. cerevisiae (12,15,31) and C. albicans (19,20). Our results showed that strain 5674 was only twofold more resistant to R6G than was strain 5457 (Fig.…”
Section: Vol 53 2009mentioning
confidence: 88%
“…To test this possibility in the GPI2 heterozygote, we studied the efflux of the fluorescent dye, R6G. Although R6G and azoles do not share a common pathway for influx (20), they are effluxed out via the same mechanism (21). R6G influx was first monitored to confirm that variation in R6G influx does not lead to any observed difference in the efflux pattern of R6G.…”
Section: Gpi2 Mutant Shows An Up-regulation Of Ergosterol Biosynthesimentioning
confidence: 99%
“…Panel ii, R6G efflux assay was done to see if the efflux of R6G varied in the two strains. R6G is a good substrate of the multidrug pumps that also efflux out azoles in C. albicans (21). The two strains exhibited similar levels of R6G efflux in the absence as well as presence of glucose (Glc).…”
Section: Gpi2 Disruption Leads To Defective Hyphal Morphogenesis Becamentioning
confidence: 99%